Oceanographic parameters associated with spatial occurrence of cephalopods in standardized demersal fishing trawls in the NE Atlantic - Daniel Oesterwind; Anne Marie Power; Esther Abad; Gregoire Certain; Nikolaos Fotiadis; Alexey Golikov; Ángel F. González; Vladimir Laptikhovsky; Silvia S. Monteiro; Carlos Montero-Castaño; Ana Moreno; Hassan Moustahfid; et al. (Marine Biology, 2026)
In this work, the environmental occurrence ranges of different European cephalopod species are described for the whole NE Atlantic shelf including the greater North Sea and Baltic Sea. This is done based on the environmental parameters collected in-situ during surveys that caught commercially important cephalopod species (1990–2022). Results are supplemented and compared with information available in the published literature and are discussed in relation to available habitat across the range, survey design, etc., and, in particular, which species are most likely to be affected by climate change. Our analyses illustrate that Loligo forbesii occupies a broader depth range than Loligo vulgaris and Alloteuthis spp. Because L. forbesii occurs further offshore and at greater depths, this species is likely more resilient to warming than the other loliginids in our study. Octopus vulgaris is documented in areas close to the coast with a more southerly distribution, whereas Eledone cirrhosa occurs further north and further away from the coast. Eledone cirrhosa occurs at lower temperatures and has a much broader depth range, which may provide resilience against warming. By contrast, both ommastrephid squid species ( Illex coindetii and Todaropsis eblanae ) showed a very similar tolerance to the three environmental variables (salinity, temperature, depth). This information should contribute to future species distribution modelling by allowing validation of realistic results against each species’ range, habitat requirements, and environmental ranges, while appreciating the data limitations caused by the timing and gear used in the survey cruises that supply occurrence and density data.

Large-scale carbon storage in the deep-sea through cold-water coral mounds off the Campeche Bank, Gulf of Mexico - L. Greiffenhagen; J. Titschack; C. Wienberg; L. H. De Clippele; L. Matos; J. Gafeira; A. Schröder-Ritzrau; K. Arul; N. Frank; D. Hebbeln (Coral Reefs, 2026)
Reef-building cold-water corals form large seabed structures known as coral mounds. As demonstrated in studies from the Northeast Atlantic and Mediterranean Sea, coral mounds accumulate large amounts of carbon(ate). However, beyond the scale of individual mounds, long-term accumulation of both organic (C org ) and inorganic carbon (C inorg ) at the mound province scale remains poorly quantified. In this study, we investigate the Campeche Mound Province, southern Gulf of Mexico, which consists of interconnected coral mound ridges covering an area of > 40 km 2 . Using sediment cores, we reconstruct total carbon (C org and C inorg ) accumulation in the Campeche Mounds over the past ~ 250 kyr. The results show mean total carbon accumulation rates of 0.5–5.6 g C cm −2 kyr −1 . This is three to nine times higher than on the surrounding seafloor. We then upscale obtained carbon concentration data to the entire mound province using high-resolution bathymetry and the CoMMa toolbox, a novel morphometric mapping tool. The total carbon storage of the Campeche Mounds amounts to an estimated 18.5 megatons of carbon that is transferred to the long-term carbon cycle and immobilised for millions of years. For the first time, we present a combination of core-based analysis and spatial mapping. Through accounting for different approaches and time scales, we provide reliable value ranges for carbon accumulation rates in coral mounds. The Campeche Mound Province is not fully mapped and likely much larger, highlighting the substantial, albeit overlooked long-term carbon burial through benthic deep-sea ecosystems in the southern Gulf of Mexico and beyond.

Nanoplastics influence on toxic metal bioaccumulation and antioxidant responses in Lactuca sativa L. irrigated with treated wastewater - A.M. Barreiros; H.F. Silva; L. Araújo; J. Coelho; C.M. Oliveira; N. Silva; M. Matos; S. Piçarra (Science of The Total Environment, 2026)

Circularity strategies for steel in the EU: Insights from consolidated material flows data - L. Ciacci; J. Fellner; C.T. Matos; T. Maury; F. Mathieux (Resources, Conservation and Recycling, 2026)

Migration of ionic and nanoparticulate zinc from nanocellulose/ZnO nanoparticle films: morphology-dependent behaviour and modelling - Ana Rita Mendes; Otmar Geiss; Ivana Bianchi; Jessica Ponti; Ana Matos; Cristina L. M. Silva; Fátima Poças (Food Additives & Contaminants: Part A, 2026)

The first transcriptome of the diaphanous deep-sea hatchetfish Sternoptyx diaphana Hermann, 1781 (Teleostei: Sternoptychidae) - André Gomes-dos-Santos; Daniel Moita; David Barros-García; André M. Machado; Ana Matos; Nair Vilas-Arrondo; L. Filipe C. Castro; Elsa Froufe (Marine Genomics, 2026)

Corrigendum to “Hydrothermal geochemical signatures in zircon as a pathfinder for IOCG mineralization: An example from the Carajás Mineral Province (Brazil)” [J. Geochem. Explor. 281,107934 (2026)] - Maurício L. Borba; Colombo C. Tassinari; Fernando M. Matos; John M. Hanchar; Fernando Tornos; Sergio Huhn; Kei Sato (Journal of Geochemical Exploration, 2026)

Meta-analytic value function and habitat risk-based assessment of ecosystem service values in a Natura 2000 area - M.I. Bastos; P.C. Roebeling; S. Villasante; F.L. Alves; L. Magalhães Filho; F.A. Matos (Ecosystem Services, 2026)

Identification of gene conversion events in horse IGHV suggests preferential hotspots for diversification - Juliana Edelvacy Lima Pinto; João Henrique Brandão Gervásio; Joseph Chi-fung Ng; Adriano Gomes-Silva; Herbert L. de Matos Guedes; Luiz Cunha; Leda R. Castilho; Jerson Lima da Silva; Glória Regina Franco; Carlena Navas; Liza Figueiredo Felicori (Immunogenetics, 2026)
The humoral immune response relies on a diverse antibody repertoire, which is expanded through processes such as somatic hypermutation, class-switch recombination and gene conversion. These processes are primarily mediated by activation-induced cytidine deaminase (AID). Gene conversion generates diversity in immunoglobulin heavy and light chains (IGHVs) in species such as chickens and rabbits, though it has not been widely studied. Since 80% of the equine IGHV repertoire originates from only three functional gene segments, we examined gene conversion events in horses to assess their role in antibody diversification. Using a modified version of BrepConvert, which optimized analysis time, we identified gene conversion events in 6.9% of immunoglobulin sequences. The results showed a local preference, with most events occurring at the beginning of framework region 1 (FR1) and within complementarity-determining region 2 (CDR2). Pseudogenes IGHV4-35, IGHV4-53, and IGHV4-38 were utilized most frequently, while functional genes IGHV4-21, IGHV4-22, and IGHV4-29 exhibited the highest event frequencies. Interestingly, while most mismatched regions were only three nucleotides long, 91% of these events are flanked by specific sequences (six nucleotides at the 5′ end and one nucleotide at the 3′ end). Furthermore, functional pseudogene pairs often share identical leader regions of 5–26 nucleotides, suggesting expanded events. We also identified a potential association between these events and local non-B DNA conformations, as well as with the zinc finger protein ZNF691, which supports the involvement of DNA-binding factors. Together, these findings demonstrate that gene conversion significantly contributes to equine antibody diversity by targeting specific IGHV regions.

Melatonin Alleviates Aluminum Toxicity in Pfaffia glomerata by Modulating Tolerance Mechanisms - Michelle M. V. Almeida; Juliane M. Henschel; Tatiane D. Silva; Luiza E. G. Monteiro; Mateus S. Rodrigues; Tadeu R. Oliveira; Auxiliadora O. Martins; Sérgio H. S. Felipe; Evandro A. Fortini; Elyabe M. Matos; Lyderson F. Viccini; Diego S. Batista; et al. (Journal of Plant Growth Regulation, 2026)
Aluminum (Al) toxicity is the main factor limiting agricultural production in acidic soils around the world. In this scenario, melatonin (MET) has emerged as a promising approach to alleviate Al toxicity. Thus, we investigated morphophysiological responses of Pfaffia glomerata (Spreng.) Pedersen, a medicinal plant, to Al toxicity and MET application. Plants were grown in vitro for 40 days in MS medium (control) supplemented with Al, MET, and Al + MET. Aluminum had genotoxic effects, inducing DNA damages and endoreduplication, which resulted in growth arrest, mainly in roots. Al also decreased the photosynthetic rate and the contents of pigments, carbohydrates, amino acids, and proteins. On the other hand, all these effects were improved in plants supplemented with MET. This is supported by the up-accumulation of proteins involved in organic acids exudation (AHA2), photosynthesis (transketolase, rubisco activase, and photosystem I P700 apoprotein A2), amino acid biosynthesis (chorismate synthase 1 and aspartokinase/homoserine dehydrogenase), and cell expansion and differentiation (rough sheath 2, beta tubulin b6, and tubulin beta chain-like). Moreover, MET enhanced CAT, SOD, and GABA, reinforcing its antioxidant role and reducing DNA damage and endoreduplication, which preserved QC identity and root elongation. Al toxicity impaired growth and carbon–nitrogen metabolism, whereas MET mitigated these effects by boosting photosynthesis, antioxidant defenses, and Al sequestration, decreasing Al adherence to roots. Thus, MET serves as a protective molecule against Al toxicity in P. glomerata .

Land-use legacies drive distinct recovery trajectories and persistently shape the taxonomic and functional composition of tree communities - Vanessa de Souza Moreno; Fabio A.R. Matos; Ricardo G. César; Gabriel D. Colleta; Elisa Díaz García; Robin L. Chazdon; Pedro H.S. Brancalion (Forest Ecology and Management, 2026)

Prospection of Autochthonous Lactic Acid Bacteria Displaying Probiotic Potential to Enhance Colossoma macropomum Larvae Growth and Immunoprotection Against Aeromonas hydrophila - Thayná M. dos Santos; Layana A. B. Pereira; Laine P. C. dos Santos; Andrya L. Lopes; Larissa A. F. Sampaio; Graziella V. G. de Matos Silva; Juliana N. Ferreira; Gleika T. J. Dos Reis; Jonny B. Teixeira; Raimundo J. T. Diniz‐Neto; Laura G. M. de Carvalho; Michelle Midori Sena Fugimura; et al. (Journal of Fish Diseases, 2026)
This study assessed the functional potential of autochthonous lactic acid bacteria isolated from the gastrointestinal tract of tambaqui ( Colossoma macropomum ) as larviculture probiotics. Five strains were selected and identified as belonging to the genus Weissella . In vitro assays revealed high tolerance to acidic pH (2.0–3.0), resistance to bile salts (10%), biofilm formation capacity, hydrophobicity and direct Aeromonas hydrophila inhibition. In in vivo tests, strains M13 and M14 promoted significant increases in tambaqui survival (72.2% and 68.7%; p

Hydrothermal geochemical signatures in zircon as a pathfinder for IOCG mineralization: An example from the Carajás Mineral Province (Brazil) - Maurício L. Borba; Colombo C. Tassinari; Fernando M. Matos; John M. Hanchar; Fernando Tornos; Sergio Huhn; Kei Sato (Journal of Geochemical Exploration, 2026)

Staphylococcus aureus in food safety: antimicrobial resistance, detection technologies, and future perspectives - Joselene C. Nunes Nascimento; Verônica O. Alvarenga; Bruno N. Paulino; Adriana B. de Cerqueira e Silva; Juliana R. Matos; Iuri L. dos Santos Rosário; Ivo Henrique P. Andrade; José Givanildo Silva; Marion Costa (Critical Reviews in Food Science and Nutrition, 2026)

Chlorophyll- a dynamics in the lower Amazon River: insights from in situ and hyperspectral remote sensing using OCI-PACE - Aline de Matos Valerio; João L. Montanari; Milton Kampel; Nicholas D. Ward; Jeffrey E. Richey; Alan C. Cunha (International Journal of Remote Sensing, 2026)

Characterization and modeling approach for planning restoration strategies in a complex basin affected by acid mine drainage - Jonatan Romero-Matos; Laura Sánchez-López; Rafael León; Robert L. Runkel; D. Kirk Nordstrom; Carlos R. Cánovas; Francisco Macías; José Miguel Nieto (Journal of Environmental Management, 2026)

Bovine and ovine deltapapillomavirus coinfection associated with equine sarcoid - E. L. Pereira; G. R. Pereira; M. L. de Osório; J. L. A. Terra; J. B. Gayger; J. S. Gularte; M. Demoliner; V. M. A. G. Pereira; M. Filippi; Q. S. de Matos; A. Tessman; C. W. Canal; et al. (Brazilian Journal of Microbiology, 2025)

Evaluation of different small-scale constructed wetlands cultivated with ultrashort hydraulic retention time and reduced operational control - R. A. Crippa; M. S. Ázara; M. P. Matos; A. T. Matos; R. Fia; L. C. Lima; A. L. P. Valácio; T. R. Silva (International Journal of Environmental Science and Technology, 2025)

Tides of rebirth: A stratigraphic perspective on the Lazarus effect in freshwater bivalves in the Aptian-Albian Romualdo Formation, Araripe Basin, Brazil - Marcello G. Simões; Vitor B. Guerrini; Victor R. Silva; Filipe G. Varejão; Suzana A. Matos; Mariza G. Rodrigues; Lucas V. Warren; Mario L. Assine; Franz T. Fürsich (Cretaceous Research, 2025)

Mathematical modeling of multicomponent extraction of metal ions by polymer membranes - M. B. de Vilhena; B. C. de Matos Junior; J. L. Ferreira; S. de A. Cardoso; B. M. Viegas; J. N. N. Quaresma; J. A. da S. Souza; E. N. Macêdo (International Journal of Environmental Science and Technology, 2025)

Neurological lesions in cervids: A study in Portugal - M.A. Pires; J. Macêdo; F. Seixas; A. Gama; M. de Lurdes Pinto; A. Alves; I. Pires; A. Cristina Matos; L. Figueira; C. Lima; P. Mendonça; P. Carvalho; et al. (Journal of Comparative Pathology, 2025)

Habitat Preference of Risso's Dolphins ( Grampus griseus ) off the South Coast of Portugal - Miguel P. Martins; Fábio L. Matos; André Cid; Guilherme Estrela; Alicia Quirin; Francisco O. Borges; Joana Castro (Marine Mammal Science, 2025)
Information on the occurrence and ecology of Risso's dolphins off the southern coast of Portugal is limited and poorly understood. This study investigated the occurrence of this species in the Algarve via presence‐absence models. In total 63 Risso's dolphin sightings were recorded with an average group size of 10 animals and a presence of immature animals in most groups (73.02%). Generalized Additive Models were fitted to test how static and dynamic oceanographic variables affected Risso's dolphin occurrence between 2010 and 2020, from a presence‐absence dataset. The optimal model showed that Risso's dolphins' probability of occurrence was higher close to the coast, and positively related to sea surface temperature, reaching a maximum presence probability between 22°C and 24°C. A positive but nonsignificant relationship between chlorophyll‐a concentration with 1 month time lag and Risso's dolphin presence was also detected. This study provides a first step to understanding habitat preference of Risso's dolphins in the south of Portugal and identifies this area's importance for the species.

Insights into the thermal stability properties of two hardwoods from the Amazon rainforest - L. de Souza-Cavalcante; F. Guerrero; J. Anglada-Rivera; Y. Leyet; F. M. A. da Silva; G. Q. Ramos; R. Matos; H. D. da Fonseca Filho (Journal of the Indian Academy of Wood Science, 2025)

Enhancing Sea Wave Monitoring Through Integrated Pressure Sensors in Smart Marine Cables - Tiago Matos; Joao L. Rocha; Marcos S. Martins; Luis M. Gonçalves (Journal of Marine Science and Engineering, 2025)
The need for real-time and scalable oceanographic monitoring has become crucial for coastal management, marine traffic control and environmental sustainability. This study investigates the integration of sensor technology into marine cables to enable real-time monitoring, focusing on tidal cycles and wave characteristics. A 2000 m cable demonstrator was deployed off the coast of Portugal, featuring three active repeater nodes equipped with pressure sensors at varying depths. The goal was to estimate hourly wave periods using fast Fourier transform and calculate significant wave height via a custom peak detection algorithm. The results showed strong coherence with tidal depth variations, with wave period estimates closely aligning with forecasts. The wave height estimations exhibited a clear relationship with tidal cycles, which demonstrates the system’s sensitivity to coastal hydrodynamics, a factor that numerical models designed for open waters often fail to capture. The study also highlights challenges in deep-water monitoring, such as signal attenuation and the need for high sampling rates. Overall, this research emphasises the scalability of sensor-integrated smart marine cables, offering a transformative opportunity to expand oceanographic monitoring capabilities. The findings open the door for future real-time ocean monitoring systems that can deliver valuable insights for coastal management, environmental monitoring and scientific research.

Impact chains for the deep seafloor: assessing pressures footprint under limited knowledge and uncertainty - Fábio L. Matos; Ana Hilário; Heliana Teixeira (Frontiers in Marine Science, 2025)
Pressures on the marine environment threaten biodiversity, ecosystem functions and services. Current marine environmental policies, such as the European Marine Strategy Framework Directive, require the assessment of combined effects and the application of ecosystem-based management approaches to maintain or achieve Good Environmental Status (GES) of marine ecosystems. We mapped the major activities and pressures affecting deep-sea benthic habitats in the mainland component of the Portuguese EEZ to assess their combined effects and support decision-making on management and conservation. Activities related to marine traffic, fisheries, and climate change processes are among the most prevalent in the study area. As a data-poor case study, most of the pressure layers were only partially mapped due to a lack of information or the inadequacy of the available data on activities to derive suitable proxies of pressure intensity. Pressures related to chemical changes, chemicals and other pollutants were the most widespread, while abrasion and damage were the most geographically limited. Endogenic pressures dominate in bathyal benthic habitats and decrease their prevalence with depth, while exogenic pressures are more widespread in the abyss than in the bathyal area. Benthic habitats in the bathyal zone, closer to the 200-meter bathymetric contour, consistently exhibited higher combined effect scores, suggesting higher risk of potential impacts on these ecosystem components. Research directed towards these areas is required to assess the state of these habitats and develop conservation and restoration measures, if necessary, to achieve GES. A continuous support for open-access databases containing high-quality, standardized, and harmonized marine data is crucial for future assessments of the combined effects of human pressures on deep-sea ecosystems.

Modelling the Distribution of Key Mediterranean Gorgonians: An Ensemble Approach to Unravel Broad‐Scale Patterns and Guide Conservation Efforts - Laura Figuerola‐Ferrando; David Amblas; Fábio L. Matos; Yanis Zentner; Joaquim Garrabou; Cristina Linares (Journal of Biogeography, 2025)
Aim Determining the species distribution and factors shaping it is a major challenge for conservation planning. Ecological niche models (ENMs) facilitate the comprehension of how environmental factors may influence species occurrence, providing spatially explicit information relevant to conservation. Therefore, our aim was to estimate the potential distribution of key habitat‐forming Mediterranean gorgonians, whose conservation would protect many co‐occurring species. Location Mediterranean Sea. Methods We modelled the potential distribution of the Mediterranean gorgonians Eunicella singularis , Eunicella cavolini , Paramuricea clavata and Corallium rubrum , using an ensemble ENM that combines nine algorithms. An extensive dataset of presence records (> 4378) collected through scientific surveys and citizen‐science was intersected with oceanographic and topographic information within the coralligenous habitat depth range ( Results The model identified higher habitat suitability for the occurrence of each gorgonian species in the NW Mediterranean, with roughness and temperature as the main drivers of their distribution. Conversely, the poorly sampled SE Mediterranean showed low habitat suitability, although there is a greater uncertainty associated with this estimate. The combined potential distribution of the four species is estimated to cover a quarter of Mediterranean shallow and mesophotic waters, but only 19% was included within protected areas. Main Conclusions The habitat suitability and uncertainty maps provide a valuable tool for the conservation and management of Mediterranean gorgonian species by offering spatially explicit information critical for marine spatial planning. The model estimates of habitat suitability showed low uncertainty for most of the study area, with few exceptions in the SE Mediterranean. Further studies, particularly in the SE Mediterranean will contribute to validate these results and will provide new information to improve future modelling efforts.

When a name changes everything: taxonomy and conservation of the Atlantic bushmaster ( Lachesis Daudin, 1803) (Serpentes: Viperidae: Crotalinae) - Breno Hamdan; Sandro L. Bonatto; Dennis Rödder; Victor Corrêa Seixas; Rogério Mercês Ferreira Santos; Diego José Santana; Larissa Gonçalves Machado; Jessica Matos Kleiz-Ferreira; Marco A. de Freitas; Rodrigo Castellari Gonzalez; Thabata Cavalcante; Moisés Barbosa de Souza; et al. (Systematics and Biodiversity, 2024)

From agroindustrial waste to nutraceuticals: Potential of mango seed for sustainable product development - Eliseo Cárdenas-Hernández; Cristian Torres-León; Mónica L. Chávez-González; Rafael Matos Ximenes; Teresinha Gonçalves da Silva; Juan A. Ascacio-Valdés; José L. Martínez-Hernández; Cristóbal N. Aguilar (Trends in Food Science & Technology, 2024)

Unsupervised segmentation for sandstone thin section image analysis - Rayan T. C. M. Barbosa; E. L. Faria; Matheus Klatt; Thais C. Silva; Juliana. M. Coelho; Thais F. Matos; Bernardo C. C. Santos; J. L. Gonzalez; Clécio R. Bom; Márcio P. de Albuquerque; Marcelo P. de Albuquerque (Computational Geosciences, 2024)

Comparative life cycle assessment of non-thermal plasma for the removal of pharmaceuticals from wastewater - E. Surra; P. Paíga; I. Baptista; R. Jorge; L. Marinheiro; S. Löblich; C. Delerue-Matos (Journal of Environmental Management, 2024)

Influence of Dolphin-Watching Tourism Vessels on the Whistle Emission Pattern of Common Dolphins and Bottlenose Dolphins - Ana A. Silva; Joana Castro; André Cid; Sérgio M. Jesus; Fábio L. Matos (Oceans, 2024)
Recent years have seen a notable rise in dolphin-watching boat activities along the Algarve coast in Portugal, potentially affecting the common dolphin (Delphinus delphis) and bottlenose dolphin (Tursiops truncatus) local populations. This study examines the impact of increasing underwater noise levels from these boats on dolphin vocalizations. Field recordings were conducted from June to September 2022, analyzing dolphin whistles in various boat presence scenarios. The results indicate significant changes in whistle-frequency characteristics with boat presence, including increased start, low, and high frequencies, alongside a decrease in the number of inflection points in modulated whistles. The changes might negatively impact dolphin populations viability, underscoring the need for further research. Additionally, improved mitigation strategies may be necessary to reduce the potential negative effects of dolphin watching on cetacean communication and behavior in the Algarve region.

Left atrial fractional shortening in cats: a comparison between two echocardiographic views - A. Machado; C. Partington; J. Silva; L. Gardner; J. Novo Matos (Journal of Veterinary Cardiology, 2024)

Soil carbon stock changes in a crop-livestock-forestry integration in Southern Goiás State, Brazil - B. E. Madari; P. S. Matos; J. M. Oliveira; M. T. M. Carvalho; A. L. R. Silveira; P. L. O. A. Machado; W. A. Araujo; M. M. B. Siqueira; T. M. Ferraresi; F. M. C. Freitas; P. V. Rizzo; R. R. Silva; et al. (Agroforestry Systems, 2024)

Correction: Effects of individual traits vs. trait syndromes on assemblages of various herbivore guilds associated with central European Salix - Jing V. Leong; Priscila Mezzomo; Petr Kozel; Tereza Volfová; Paola de Lima Ferreira; Carlo L. Seifert; Phillip T. Butterill; Inga Freiberga; Jan Michálek; Pável Matos-Maraví; Alexander Weinhold; Marica T. Engström; et al. (Oecologia, 2024)

Effects of individual traits vs. trait syndromes on assemblages of various herbivore guilds associated with central European Salix - Jing V. Leong; Priscila Mezzomo; Petr Kozel; Tereza Volfová; Paola de Lima Ferreira; Carlo L. Seifert; Phillip T. Butterill; Inga Freiberga; Jan Michálek; Pável Matos-Maraví; Alexander Weinhold; Marica T. Engström; et al. (Oecologia, 2024)

Invasive non-native species in Brazil: an updated overview - Rafael D. Zenni; Sílvia R. Ziller; Clarissa A. da Rosa; Rafael B. Sühs; Patricia B. Puechagut; Beloni T. P. Marterer; Gustavo Heringer; Ana Carolina L. de Matos; Marina L. Bueno; Jonathan W. Almeida; Carlos H. T. Silva; José Renato Legracie-Júnior; et al. (Biological Invasions, 2024)

Ultrasound-assisted extraction of bioactive compounds from goji berries: Optimization, bioactivity, and intestinal permeability assessment - Filipa Teixeira; Ana Margarida Silva; Stefania Sut; Stefano Dall'Acqua; Oscar L. Ramos; Alessandra B. Ribeiro; Ricardo Ferraz; Cristina Delerue-Matos; Francisca Rodrigues (Food Research International, 2024)

Nonthermal high-pressure microalgae extracts: A new source of natural ingredients for cosmetics - Mónica P. Garcia; Ana Regueiras; Graciliana Lopes; Gabriela Matos; Lucília P. da Silva; Mariana T. Cerqueira; Helena Cardoso; Nádia Correia; Jorge A. Saraiva; Joana L. Silva; Rosário Martins; Alexandra P. Marques (Algal Research, 2024)

Assessing the dynamics of common dolphin ( Delphinus delphis ) mother‐calf pairs along the south coast of Portugal using unmanned aerial vehicles - Joana Castro; André Cid; Alicia Quirin; Fábio L. Matos; Rui Rosa; Heidi C. Pearson (Marine Mammal Science, 2024)
Maternal grouping dynamics involve trade‐offs between: (1) infant protection from predation (predation hypothesis), (2) infant protection from male harassment (infant safety hypothesis), and (3) reducing scramble competition for prey resources (foraging‐type scramble competition hypothesis). Using unmanned aerial vehicles, we assessed grouping dynamics in common dolphin ( Delphinus delphis ) groups containing mother‐calf pairs to address these hypotheses. We analyzed social aspects and structural group elements using generalized additive mixed models and modeled group formation using multinomial generalized estimating equations. Calf proportion was higher in very compact groups and in groups of 10–20 individuals but decreased in larger groups. The frequency of socio‐sexual behaviors increased in larger groups and decreased in groups with higher calf proportion. Calf distance to its nearest neighbor decreased with increasing group size and cohesion. With a higher proportion of calves, scatter (versus parallel) formation was less frequent. A calf's nearest neighbor was most often (55.4%) a nonmother. Calves showed a preference for being in the front center of the group. These results offer strong support for the predation and infant safety hypotheses and partial support for the foraging‐type scramble competition hypothesis. This work provides insight into the adaptive function of maternal strategies in a small delphinid.

Geography and ecology shape the phylogenetic composition of Amazonian tree communities - Bruno Garcia Luize; David Bauman; Hans ter Steege; Clarisse Palma‐Silva; Iêda Leão do Amaral; Luiz de Souza Coelho; Francisca Dionízia de Almeida Matos; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Florian Wittmann; Carolina V. Castilho; Marcelo de Jesus Veiga Carim; et al. (Journal of Biogeography, 2024)
Aim Amazonia hosts more tree species from numerous evolutionary lineages, both young and ancient, than any other biogeographic region. Previous studies have shown that tree lineages colonized multiple edaphic environments and dispersed widely across Amazonia, leading to a hypothesis, which we test, that lineages should not be strongly associated with either geographic regions or edaphic forest types. Location Amazonia. Taxon Angiosperms (Magnoliids; Monocots; Eudicots). Methods Data for the abundance of 5082 tree species in 1989 plots were combined with a mega‐phylogeny. We applied evolutionary ordination to assess how phylogenetic composition varies across Amazonia. We used variation partitioning and Moran's eigenvector maps (MEM) to test and quantify the separate and joint contributions of spatial and environmental variables to explain the phylogenetic composition of plots. We tested the indicator value of lineages for geographic regions and edaphic forest types and mapped associations onto the phylogeny. Results In the terra firme and várzea forest types, the phylogenetic composition varies by geographic region, but the igapó and white‐sand forest types retain a unique evolutionary signature regardless of region. Overall, we find that soil chemistry, climate and topography explain 24% of the variation in phylogenetic composition, with 79% of that variation being spatially structured ( R 2 = 19% overall for combined spatial/environmental effects). The phylogenetic composition also shows substantial spatial patterns not related to the environmental variables we quantified ( R 2 = 28%). A greater number of lineages were significant indicators of geographic regions than forest types. Main Conclusion Numerous tree lineages, including some ancient ones (>66 Ma), show strong associations with geographic regions and edaphic forest types of Amazonia. This shows that specialization in specific edaphic environments has played a long‐standing role in the evolutionary assembly of Amazonian forests. Furthermore, many lineages, even those that have dispersed across Amazonia, dominate within a specific region, likely because of phylogenetically conserved niches for environmental conditions that are prevalent within regions.

Feeding behaviour of feedlot lambs offered different amounts of concentrate with or without protected fat - Cláudia L.S. Lima; Douglas dos S. Pina; Gleidson G.P. de Carvalho; Henry D.R. Alba; Maria L.G.M. L. de Araújo, Susiane de C. Matos; Stefanie A. Santos; Maria L.O. Chaves; Carlindo S. Rodrigues; Manuela S.L. Tosto (Applied Animal Behaviour Science, 2024)

The decline and death of Canary Island date palms in México City is associated with subgroup 16SrIV-D phytoplasmas - C. F. Ortiz-García; D. Alvarado-Rosales; C. Oropeza; L. de L. Saavedra-Romero; S. Aranda-Ocampo; A. Almaraz-Sánchez; A. Quezada-Salinas; A. Equihua-Martínez; S. E. García-Díaz; M. Narváez; G. Nic-Matos; P. J. Palma-Cancino; et al. (Australasian Plant Pathology, 2024)

Gone with the stream: Functional connectivity of a cold‐water coral at basin scale - Fábio L. Matos; Jacopo Aguzzi; Joan B. Company; Marina R. Cunha (Limnology and Oceanography, 2024)
Lophelia pertusa reefs are vulnerable deep‐sea ecosystems and their ecological integrity partly depends on the connectivity and availability of suitable habitat. Moreover, connectivity is a guiding principle in marine conservation planning, particularly for spatial prioritization and for the design of networks of marine protected areas. We estimated the functional seascape connectivity of L. pertusa in the Mediterranean Sea and provide a framework for prioritizing habitat areas for the species conservation. These goals were achieved by simulating transport and potential dispersal of virtual larvae using biophysical modeling and assessing habitat availability based on the suitability and spatial arrangement of the seascape and inter‐annual climatological variability. Habitat availability was estimated using a network analysis and accounting for the attributes of habitat areas (i.e., size and quality). The connectivity among Mediterranean ecoregions was weak and an increase in the frequency of climate‐driven events (e.g., dense shelf water cascading) may worsen this scenario. However, the potential exchange of larvae between patches within the same ecoregion was high, favoring populations resilience to local disturbances. The analysis of habitat availability allowed identifying important habitat areas for the connectivity of the L. pertusa including the Gulf of Lion, the Apulian and Sicily Island continental margin. Some of the habitat areas identified as important for the connectivity of the L. pertusa are exposed to intense anthropogenic pressures, that may act synergistically with climate change imposing greater challenges to species conservation. These habitat areas may be prioritized in future management and conservation actions targeting L. pertusa .

Enhancing the taxonomic delimitation of Lippia origanoides Kunth (Verbenaceae) by analyzing volatile terpenes and molecular markers in micropropagated accessions - Laís M. Frattini; Arthur A. Oliveira; Jhoão S. Kotsubo; Íris B. Gorne; Isabel C. Silva; Jober C. E. Freitas; Cristiano F. Resende; Ana C. Mezzonato-Pires; Elyabe M. Matos; Juliana M. L. Lopes; Lyderson F. Viccini; Richard M. Grazul; et al. (Plant Cell, Tissue and Organ Culture (PCTOC), 2024)

How complex is the hidden species diversity of the teleost Plotosus genus? - Elsa Froufe; André Gomes-dos-Santos; Ana Matos; Jonathan Wilson; Salman Malakpourkolbadinezhad; Daniel D. Pereira; Randal Singer; L. Filipe C. Castro (Ichthyological Research, 2024)
The striped eel catfish, Plotosus lineatus was first described by Thunberg in 1787 from the Indo-Pacific region in the East Indian Ocean. Since then, the species has been recorded in various marine and brackish habitats in Japan, southern Korea, the Ogasawara Islands, Australia, Lord Howe Island, Palau and Yap in Micronesia, East Africa to Samoa, Madagascar, Red Sea and the Persian Gulf. Occurrences of this species have also been registered in the Mediterranean Sea, a non-native location, indicating a possible biological invasion event. Despite its long history, the taxonomic status of the P. lineatus species complex remains puzzling and uncertain. Here, we analysed all the available mitochondrial cytochrome c oxidase subunit 1 sequences (NCBI and BOLD) from specimens covering the current known distribution range, in an attempt to clarify the evolutionary relationships of different lineages within this species. We deduce nine monophyletic Lineages - I–IX , of P. lineatus with Kimura-2P distances ranging from 2% to 16%, with a mean intraspecific distance of 6%. Strikingly, Lineage V is composed uniquely of Mediterranean-captured individuals, with an unknown evolutionary origin. These findings strongly suggest the need for a careful species taxonomic reassessment. Some Lineages are composed of individuals from specific geographic locations (e.g., Australia and Indonesia), while others include specimens from broader geographic areas (e.g., almost all Indo-Pacific coastline). Additionally, several deposited sequences are most likely the result of morphology-based misidentifications. Due to the biological invasive potential, as well as the use of the species as a valuable physiology model, the P. lineatus species complex requires further attention. Overall our study offers a clear framework for future comparative studies of striped eel catfish individuals captured from different ecosystems.

Practical application of circularity micro-indicators to automotive plastic parts in an industrial context - Joana Matos; Sara Santos; Carla L. Simões; Carla I. Martins; Ricardo Simoes (Sustainable Production and Consumption, 2023)

Culture operational strategies for the production of methane and algal oil using ethanol vinasse effluent - Gabriele R. Conceição; Carine S. da Silva; Tatiana O. do Vale; Jacson N. dos Santos; Josilene B. T. L. Matos; Paulo F.de Almeida; Fabio A. Chinalia (Journal of Applied Phycology, 2023)

Giants of the Amazon: How does environmental variation drive the diversity patterns of large trees? - Robson Borges de Lima; Eric Bastos Görgens; Diego Armando S. da Silva; Cinthia Pereira de Oliveira; Anderson Pedro B. Batista; Rinaldo L. Caraciolo Ferreira; Flavia R. C. Costa; Renato A. Ferreira de Lima; Perseu da Silva Aparício; Jadson Coelho de Abreu; José Antônio Aleixo da Silva; Aretha Franklin Guimaraes; et al. (Global Change Biology, 2023)
For more than three decades, major efforts in sampling and analyzing tree diversity in South America have focused almost exclusively on trees with stems of at least 10 and 2.5 cm diameter, showing highest species diversity in the wetter western and northern Amazon forests. By contrast, little attention has been paid to patterns and drivers of diversity in the largest canopy and emergent trees, which is surprising given these have dominant ecological functions. Here, we use a machine learning approach to quantify the importance of environmental factors and apply it to generate spatial predictions of the species diversity of all trees (dbh ≥ 10 cm) and for very large trees (dbh ≥ 70 cm) using data from 243 forest plots (108,450 trees and 2832 species) distributed across different forest types and biogeographic regions of the Brazilian Amazon. The diversity of large trees and of all trees was significantly associated with three environmental factors, but in contrasting ways across regions and forest types. Environmental variables associated with disturbances, for example, the lightning flash rate and wind speed, as well as the fraction of photosynthetically active radiation, tend to govern the diversity of large trees. Upland rainforests in the Guiana Shield and Roraima regions had a high diversity of large trees. By contrast, variables associated with resources tend to govern tree diversity in general. Places such as the province of Imeri and the northern portion of the province of Madeira stand out for their high diversity of species in general. Climatic and topographic stability and functional adaptation mechanisms promote ideal conditions for species diversity. Finally, we mapped general patterns of tree species diversity in the Brazilian Amazon, which differ substantially depending on size class.

Comparative analysis of micro level indicators for evaluating the progress towards a circular economy - Joana Matos; Carla Martins; Carla L. Simões; Ricardo Simoes (Sustainable Production and Consumption, 2023)

Temporo-basal sulcal connections: a manual annotation protocol and an investigation of sexual dimorphism and heritability - Kevin de Matos; Claire Cury; Lydia Chougar; Lachlan T. Strike; Thibault Rolland; Maximilien Riche; Lisa Hemforth; Alexandre Martin; Tobias Banaschewski; Arun L. W. Bokde; Sylvane Desrivières; Herta Flor; et al. (Brain Structure and Function, 2023)

Magnetic solid phase extraction as a nonchromatographic method for the quantification of ultratrace inorganic arsenic in rice by inductively coupled plasma-optical emission spectrometry (ICP OES) - Francisco L.F. da Silva; Francisco E.H. Lima; Davino M. Andrade Neto; Fernando L. de Menezes; Lillian M.U.D. Fechine; Abdullah Akhdhar; Livia P.D. Ribeiro; Ana R.A. Nogueira; Pierre B.A. Fechine; Gisele S. Lopes; Wladiana O. Matos (Food Chemistry, 2023)

Assessment of Habitat Suitability for Common Cockles in the Ria the Aveiro Lagoon Under Average and Projected Environmental Conditions - Fábio L. Matos; Nuno Vaz; Ana Picado; João M. Dias; Francisco Maia; Miguel B. Gaspar; Luísa Magalhães (Estuaries and Coasts, 2023)

Geographic patterns of tree dispersal modes in Amazonia and their ecological correlates - Diego F. Correa; Pablo R. Stevenson; Maria Natalia Umaña; Luiz de Souza Coelho; Diógenes de Andrade Lima Filho; Rafael P. Salomão; Iêda Leão do Amaral; Florian Wittmann; Francisca Dionízia de Almeida Matos; Carolina V. Castilho; Oliver L. Phillips; Juan Ernesto Guevara; et al. (Global Ecology and Biogeography, 2023)
Aim To investigate the geographic patterns and ecological correlates in the geographic distribution of the most common tree dispersal modes in Amazonia (endozoochory, synzoochory, anemochory and hydrochory). We examined if the proportional abundance of these dispersal modes could be explained by the availability of dispersal agents (disperser‐availability hypothesis) and/or the availability of resources for constructing zoochorous fruits (resource‐availability hypothesis). Time period Tree‐inventory plots established between 1934 and 2019. Major taxa studied Trees with a diameter at breast height (DBH) ≥ 9.55 cm. Location Amazonia, here defined as the lowland rain forests of the Amazon River basin and the Guiana Shield. Methods We assigned dispersal modes to a total of 5433 species and morphospecies within 1877 tree‐inventory plots across terra‐firme, seasonally flooded, and permanently flooded forests. We investigated geographic patterns in the proportional abundance of dispersal modes. We performed an abundance‐weighted mean pairwise distance (MPD) test and fit generalized linear models (GLMs) to explain the geographic distribution of dispersal modes. Results Anemochory was significantly, positively associated with mean annual wind speed, and hydrochory was significantly higher in flooded forests. Dispersal modes did not consistently show significant associations with the availability of resources for constructing zoochorous fruits. A lower dissimilarity in dispersal modes, resulting from a higher dominance of endozoochory, occurred in terra‐firme forests (excluding podzols) compared to flooded forests. Main conclusions The disperser‐availability hypothesis was well supported for abiotic dispersal modes (anemochory and hydrochory). The availability of resources for constructing zoochorous fruits seems an unlikely explanation for the distribution of dispersal modes in Amazonia. The association between frugivores and the proportional abundance of zoochory requires further research, as tree recruitment not only depends on dispersal vectors but also on conditions that favour or limit seedling recruitment across forest types.

Environmental disaster in mining areas: routes of exposure to metals in the Doce River basin - A. R. de Matos; H. T. da Silva; M. C. S. da Faria; B. M. Freire; R. M. Pereira; B. L. Batista; J. L. Rodrigues (International Journal of Environmental Science and Technology, 2022)

Lithology identification in carbonate thin section images of the Brazilian pre-salt reservoirs by the computational vision and deep learning - E. L. Faria; Juliana. M. Coelho; Thais F. Matos; Bernardo C. C. Santos; Willian A. Trevizan; J. L. Gonzalez; Clécio R. Bom; Márcio P. de Albuquerque; Marcelo P. de Albuquerque (Computational Geosciences, 2022)

Supraparticles as slow-release fertiliser in seedling potential growth of Eucalyptus urograndis and greenhouse gas flux impacts - Gabriel Goetten de Lima; Mailson Matos; Francielen Paola de Sá; Leandro Nozomi Mashiba; Washington L. E. Magalhães; Marcos Fernando Glück Rachwal; Josileia Acordi Zanatta (Environmental Science and Pollution Research, 2022)

Common dolphin (Delphinus delphis) fission–fusion dynamics in the south coast of Portugal - Joana Castro; Cláudia Faustino; André Cid; Alicia Quirin; Fábio L. Matos; Rui Rosa; Heidi C. Pearson (Behavioral Ecology and Sociobiology, 2022)

Pleurotus strains with remediation potential to remove toxic metals from Doce River contaminated by Samarco dam mine - M. P. O. Santos; M. V. N. Santos; R. S. Matos; A. S. Van Der Maas; M. C. S. Faria; B. L. Batista; J. L. Rodrigues; C. A. Bomfeti (International Journal of Environmental Science and Technology, 2022)

Bioactive compounds and hepatoprotective effect of Hancornia speciosa gomes fruit juice on acetaminophen-induced hepatotoxicity in vivo - Rosangela S. Santos; Adriano B. Chaves-Filho; Luiz A. S. Silva; Carlos A. B. Garcia; Audrey R. S. T. Silva; Silvio S. Dolabella; Silvânio S. L. da Costa; Sayuri Miyamoto; Humberto R. Matos (Natural Product Research, 2022)

Latent effects of intertidal encapsulated development on juvenile fitness of the marine snail Acanthina monodon - L. P. Salas-Yanquin; N. P. Pinilla; A. S. Matos; J. A. Bűchner-Miranda; J. M. Navarro; V. M. Cubillos; J. A. Pechenik; O. R. Chaparro (Marine Biology, 2022)

Transcriptome analysis reveals key defense-related genes upon SA induction in Cocos nucifera L. - C. Silverio-Gómez; J. Vega-Arreguín; G. Nic-Matos; M. Narváez-Cab; L. Sáenz-Carbonell; C. Oropeza (Genes & Genomics, 2022)

Coping and Adaptation in Response to Environmental and Climatic Stressors in Caribbean Coastal Communities - Julia Touza; Carmen Lacambra; Alexandra Kiss; Rosa Mato Amboage; Paula Sierra; Martin Solan; Jasmin A. Godbold; Thomas Spencer; Piran C. L. White (Environmental Management, 2021)
Cumulative and synergistic impacts from environmental pressures, particularly in low-lying tropical coastal regions, present challenges for the governance of ecosystems, which provide natural resource-based livelihoods for communities. Here, we seek to understand the relationship between responses to the impacts of El Niño and La Niña events and the vulnerability of mangrove-dependent communities in the Caribbean region of Colombia. Using two case study sites, we show how communities are impacted by, and undertake reactive short-term responses to, El Niño and La Niña events, and how such responses can affect their adaptive capacity to progressive environmental deterioration. We show that certain coping measures to climate variability currently deliver maladaptive outcomes, resulting in circumstances that could contribute to system ‘lock-in’ and engender undesirable ecological states, exacerbating future livelihood vulnerabilities. We highlight the significant role of social barriers on vulnerabilities within the region, including perceptions of state abandonment, mistrust and conflicts with authorities. Opportunities to reduce vulnerability include enhancing the communities’ capacity to adopt more positive and preventative responses based on demonstrable experiential learning capacity. However, these will require close cooperation between formal and informal organisations at different levels, and the development of shared coherent adaptation strategies to manage the complexity of multiple interacting environmental and climatic pressures.

Neurological disease caused by Oropouche virus in northern Brazil: should it be included in the scope of clinical neurological diseases? - Jannifer O. Chiang; Rafael S. Azevedo; Maria C. A. Justino; Haroldo J. Matos; Hideraldo L. S. Cabeça; Sandro P. Silva; Daniele F. Henriques; Eliana V. P. Silva; Gabriela S. S. Andrade; Pedro FC. Vasconcelos; Lívia C. Martins; Raimunda S. S. Azevedo (Journal of NeuroVirology, 2021)
We describe two neurological cases of Oropouche virus infection in northern Brazil, where the virus is endemic but neglected as a pathogen. This study reiterates the necessity of developing protocols for diagnosing infections and training medical personnel to recognize the pathogenicity of Oropouche virus in neurological infections.

Enzymatically crosslinked tyramine-gellan gum hydrogels as drug delivery system for rheumatoid arthritis treatment - Isabel Matos Oliveira; Cristiana Gonçalves; Myeong Eun Shin; Sumi Lee; Rui L. Reis; Gilson Khang; Joaquim Miguel Oliveira (Drug Delivery and Translational Research, 2021)

The hidden curve behind COVID-19 outbreak: the impact of delay in treatment initiation in cancer patients and how to mitigate the additional risk of dying—the head and neck cancer model - Leandro L. Matos; Carlos Henrique Q. Forster; Gustavo N. Marta; Gilberto Castro Junior; John A. Ridge; Daisy Hirata; Adalberto Miranda-Filho; Ali Hosny; Alvaro Sanabria; Vincent Gregoire; Snehal G. Patel; Johannes J. Fagan; et al. (Cancer Causes & Control, 2021)

Evaluation of chelating and cytoprotective activity of vanillin against the toxic action of mercuric chloride as an alternative for phytoremediation - Joelma P. da Silva; Maria do S. Costa; Fabia F. Campina; Camila F. Bezerra; Thiago S. de Freitas; Amanda K. Sousa; Celestina E. Sobral Souza; Yedda M. L. S. de Matos; Francisco N. Pereira-Junior; Irwim R. A. Menezes; Henrique D. M. Coutinho; Janaína E. Rocha (Environmental Geochemistry and Health, 2021)

NEOTROPICAL CARNIVORES: a data set on carnivore distribution in the Neotropics - Mariana Nagy‐Reis; Júlia Emi de Faria Oshima; Claudia Zukeran Kanda; Francesca Belem Lopes Palmeira; Fabiano Rodrigues de Melo; Ronaldo Gonçalves Morato; Lilian Bonjorne; Marcelo Magioli; Caroline Leuchtenberger; Fabio Rohe; Frederico Gemesio Lemos; Felipe Martello; et al. (Ecology, 2020)
Mammalian carnivores are considered a key group in maintaining ecological health and can indicate potential ecological integrity in landscapes where they occur. Carnivores also hold high conservation value and their habitat requirements can guide management and conservation plans. The order Carnivora has 84 species from 8 families in the Neotropical region: Canidae; Felidae; Mephitidae; Mustelidae; Otariidae; Phocidae; Procyonidae; and Ursidae. Herein, we include published and unpublished data on native terrestrial Neotropical carnivores (Canidae; Felidae; Mephitidae; Mustelidae; Procyonidae; and Ursidae). NEOTROPICAL CARNIVORES is a publicly available data set that includes 99,605 data entries from 35,511 unique georeferenced coordinates. Detection/non‐detection and quantitative data were obtained from 1818 to 2018 by researchers, governmental agencies, non‐governmental organizations, and private consultants. Data were collected using several methods including camera trapping, museum collections, roadkill, line transect, and opportunistic records. Literature (peer‐reviewed and grey literature) from Portuguese, Spanish and English were incorporated in this compilation. Most of the data set consists of detection data entries (n = 79,343; 79.7%) but also includes non‐detection data (n = 20,262; 20.3%). Of those, 43.3% also include count data (n = 43,151). The information available in NEOTROPICAL CARNIVORES will contribute to macroecological, ecological, and conservation questions in multiple spatio‐temporal perspectives. As carnivores play key roles in trophic interactions, a better understanding of their distribution and habitat requirements are essential to establish conservation management plans and safeguard the future ecological health of Neotropical ecosystems. Our data paper, combined with other large‐scale data sets, has great potential to clarify species distribution and related ecological processes within the Neotropics. There are no copyright restrictions and no restriction for using data from this data paper, as long as the data paper is cited as the source of the information used. We also request that users inform us of how they intend to use the data.

NEOTROPICAL ALIEN MAMMALS: a data set of occurrence and abundance of alien mammals in the Neotropics - Clarissa Alves da Rosa; Bruno R. Ribeiro; Vanesa Bejarano; Fernando Henrique Puertas; Adriana Bocchiglieri; Adriana Loeser dos Santos Barbosa; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adriele Aparecida Pereira; Adryelle Francisca de Souza Moreira; Agnis Cristiane de Souza; Aiesca Pellegrin; et al. (Ecology, 2020)
Biological invasion is one of the main threats to native biodiversity. For a species to become invasive, it must be voluntarily or involuntarily introduced by humans into a nonnative habitat. Mammals were among first taxa to be introduced worldwide for game, meat, and labor, yet the number of species introduced in the Neotropics remains unknown. In this data set, we make available occurrence and abundance data on mammal species that (1) transposed a geographical barrier and (2) were voluntarily or involuntarily introduced by humans into the Neotropics. Our data set is composed of 73,738 historical and current georeferenced records on alien mammal species of which around 96% correspond to occurrence data on 77 species belonging to eight orders and 26 families. Data cover 26 continental countries in the Neotropics, ranging from Mexico and its frontier regions (southern Florida and coastal‐central Florida in the southeast United States) to Argentina, Paraguay, Chile, and Uruguay, and the 13 countries of Caribbean islands. Our data set also includes neotropical species (e.g., Callithrix sp., Myocastor coypus , Nasua nasua) considered alien in particular areas of Neotropics. The most numerous species in terms of records are from Bos sp. ( n = 37,782), Sus scrofa ( n = 6,730), and Canis familiaris ( n = 10,084); 17 species were represented by only one record (e.g., S yncerus caffer, Cervus timorensis, Cervus unicolor, Canis latrans ). Primates have the highest number of species in the data set ( n = 20 species), partly because of uncertainties regarding taxonomic identification of the genera Callithrix, which includes the species Callithrix aurita, Callithrix flaviceps, Callithrix geoffroyi, Callithrix jacchus, Callithrix kuhlii, Callithrix penicillata , and their hybrids. This unique data set will be a valuable source of information on invasion risk assessments, biodiversity redistribution and conservation‐related research. There are no copyright restrictions. Please cite this data paper when using the data in publications. We also request that researchers and teachers inform us on how they are using the data.

Inorganic content of rock dust waste from northwest of Rio de Janeiro, Brazil: do environmental risks incur from its use as natural fertilizer? - Camila V. G. Vitó; Hellen G. Vieira; Adriano H. Ferrarez; Cibele M. S. de Almeida; Francisco L. F. da Silva; Wladiana O. Matos; Murilo de O. Souza (Environmental Monitoring and Assessment, 2020)

Pilot-Scaled Fast-Pyrolysis Conversion of Eucalyptus Wood Fines into Products: Discussion Toward Possible Applications in Biofuels, Materials, and Precursors - Mailson Matos; Bruno D. Mattos; Pedro H. G. de Cademartori; Tainise V. Lourençon; Fabrício A. Hansel; Patrícia R. S. Zanoni; Carlos I. Yamamoto; Washington L. E. Magalhães (BioEnergy Research, 2020)

Adenosine and NMDA Receptors Modulate Neuroprotection-Induced NMDA Preconditioning in Mice - Adriana B. Ghislandi; Michelle L. Garcez; Gabriela M. Zambon; Leandra C. Constantino; Douglas N. Matos; Bruna B. Pescador; Carla I. Tasca; Carina R. Boeck (Journal of Molecular Neuroscience, 2020)

Lipid composition and some bioactivities of 3 newly isolated microalgae (Tetraselmis sp. IMP3, Tetraselmis sp. CTP4, and Skeletonema sp.) - C. Cardoso; H. Pereira; J. Franca; J. Matos; I. Monteiro; P. Pousão-Ferreira; A. Gomes; L. Barreira; J. Varela; N. Neng; J. M. Nogueira; C. Afonso; et al. (Aquaculture International, 2020)

Histopathology associated with infection by Procamallanus (Spirocamallanus) inopinatus (Nematoda) in farmed Brycon cephalus (Characiformes) from Peru: a potential fish health problem - Norma L. S. Rivadeneyra; Omar Mertins; Ruben C. Cuadros; Jose C. O. Malta; Lorena V. de Matos; Patrick D. Mathews (Aquaculture International, 2020)

Modulation of P2Y2 receptors in bovine cumulus oocyte complexes: effects on intracellular calcium, zona hardening and developmental competence - E. Fonseca; P. Mesquita; C. C. Marques; M. C. Baptista; J. Pimenta; J. E. Matos; G. Soveral; R. M. L. N. Pereira (Purinergic Signalling, 2020)

Do Workers from Subspecies Acromyrmex subterraneus Prepare Leaves and Toxic Baits in Similar Ways for Their Fungus Garden? - L. C. Forti; A. P. P. Andrade; K. K. A. Sousa; R. S. Camargo; C. A. O. Matos; N. Caldato; G. C. Catalani; V. M. Ramos (Neotropical Entomology, 2020)

Can Acacia mangium and Acacia auriculiformis hinder restoration efforts in the Brazilian Atlantic Forest under current and future climate conditions? - Gustavo Heringer; Marcelo L. Bueno; João A. A. Meira-Neto; Fábio A. R. Matos; Andreza V. Neri (Biological Invasions, 2019)

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Selection of oviposition sites by ground beetles Abaris basistriata and Selenophorus seriatoporus for mass rearing purposes - Crislany L. Barbosa-Andrade; Daniel J. Andrade; Sidnéia T. S. Matos; Luciano Nogueira; Francisco J. Cividanes (BioControl, 2019)

The digestive tube of Piaractus brachypomus : gross morphology, histology/histochemistry of the mucosal layer and the effects of parasitism by Neoechinorhynchus sp. - Maria I. B. de Oliveira; Lorena V. de Matos; Lídia A. da Silva; Edsandra C. Chagas; Grazyelle S. da Silva; Ana L. S. Gomes (Journal of Fish Biology, 2019)
The objective of the present study was to describe the histology and histochemistry of the mucosal layer of the digestive tube of Piaractus brachypomus , and the histopathology associated with parasitism by Neoechinorhynchus sp. The digestive tube of P. brachypomus consists of three macroscopically distinct portions: short, rectilinear and elastic‐walled ooesophagus, J‐shaped siphon stomach and a long intestine with rectilinear and curved portions, defined by patterns of villi as foregut, midgut, and hindgut. Histological and histochemical differences were observed in the mucosal layers of the different digestive tube regions, such as intense production of neutral and acidic mucous substances in the pseudostratified mucosal epithelium of the oesophagus; positive periodic acid Schiff reagent (PAS)reactions at the apex of the columnar epithelial cells of the stomach and increased intensity of histochemical reactions in the hindgut region. Neoechinorhynchus sp. was present in 85.7% of specimens examined, with a mean intensity of 7.4 ± 6.2 (±) and abundance of 6.33. Good health of the fish indicated by high relative condition factor values ( Kn ) and occurrence of only mild to moderate alteration in the mucosal layer indicated that Neoechinorhynchus sp. exhibits low pathogenicity towards P. brachypomus hosts in farming environments, with low levels of infection.

Pre-hatching development in the intertidal zone negatively affects juvenile survival and physiology in the muricid gastropod Acanthina monodon - O. R. Chaparro; L. P. Salas-Yanquin; A. S. Matos; J. A. Bűchner-Miranda; M. W. Gray; V. M. Cubillos; J. A. Pechenik (Marine Biology, 2018)

Creation of a coastal evolution prognostic model using shoreline historical data and techniques of digital image processing in a GIS environment for generating future scenarios - Willamys R. N. de Sousa; Michael V. S. Souto; Stefanny S. Matos; Cynthia R. Duarte; Ana R. G. N. L. Salgueiro; Cláudio A. da Silva Neto (International Journal of Remote Sensing, 2018)

Fos Protein as a Marker of Neuronal Activity: a Useful Tool in the Study of the Mechanism of Action of Natural Products with Analgesic Activity - Priscila L. Santos; Renan G. Brito; João Pedro S. C. F. Matos; Jullyana S. S. Quintans; Lucindo J. Quintans-Júnior (Molecular Neurobiology, 2018)

Regenerative potential, metabolic profile, and genetic stability of Brachypodium distachyon embryogenic calli as affected by successive subcultures - T. C. Mamedes-Rodrigues; D. S. Batista; N. M. Vieira; E. M. Matos; D. Fernandes; A. Nunes-Nesi; C. D. Cruz; L. F. Viccini; F. T. S. Nogueira; W. C. Otoni (Protoplasma, 2018)

Integrated ecological–economic fisheries models—Evaluation, review and challenges for implementation - J Rasmus Nielsen; Eric Thunberg; Daniel S Holland; Jorn O Schmidt; Elizabeth A Fulton; Francois Bastardie; Andre E Punt; Icarus Allen; Heleen Bartelings; Michel Bertignac; Eckhard Bethke; Sieme Bossier; et al. (Fish and Fisheries, 2018)
Marine ecosystems evolve under many interconnected and area‐specific pressures. To fulfil society's intensifying and diversifying needs while ensuring ecologically sustainable development, more effective marine spatial planning and broader‐scope management of marine resources is necessary. Integrated ecological–economic fisheries models ( IEEFM s) of marine systems are needed to evaluate impacts and sustainability of potential management actions and understand, and anticipate ecological, economic and social dynamics at a range of scales from local to national and regional. To make these models most effective, it is important to determine how model characteristics and methods of communicating results influence the model implementation, the nature of the advice that can be provided and the impact on decisions taken by managers. This article presents a global review and comparative evaluation of 35 IEEFM s applied to marine fisheries and marine ecosystem resources to identify the characteristics that determine their usefulness, effectiveness and implementation. The focus is on fully integrated models that allow for feedbacks between ecological and human processes although not all the models reviewed achieve that. Modellers must invest more time to make models user friendly and to participate in management fora where models and model results can be explained and discussed. Such involvement is beneficial to all parties, leading to improvement of mo‐dels and more effective implementation of advice, but demands substantial resources which must be built into the governance process. It takes time to develop effective processes for using IEEFM s requiring a long‐term commitment to integrating multidisciplinary modelling advice into management decision‐making.

Importance of tissue sampling, laboratory methods, and patient characteristics for detection of Pneumocystis in autopsied lungs of non-immunosuppressed individuals - S. L. Vargas; C. Ponce; R. Bustamante; E. Calderón; G. Nevez; Y. De Armas; O. Matos; R. F. Miller; M. J. Gallo (European Journal of Clinical Microbiology & Infectious Diseases, 2017)

Variation in stem mortality rates determines patterns of above‐ground biomass in A mazonian forests: implications for dynamic global vegetation models - Michelle O. Johnson; David Galbraith; Manuel Gloor; Hannes De Deurwaerder; Matthieu Guimberteau; Anja Rammig; Kirsten Thonicke; Hans Verbeeck; Celso von Randow; Abel Monteagudo; Oliver L. Phillips; Roel J. W. Brienen; et al. (Global Change Biology, 2016)
Understanding the processes that determine above‐ground biomass ( AGB ) in Amazonian forests is important for predicting the sensitivity of these ecosystems to environmental change and for designing and evaluating dynamic global vegetation models ( DGVM s). AGB is determined by inputs from woody productivity [woody net primary productivity ( NPP )] and the rate at which carbon is lost through tree mortality. Here, we test whether two direct metrics of tree mortality (the absolute rate of woody biomass loss and the rate of stem mortality) and/or woody NPP , control variation in AGB among 167 plots in intact forest across Amazonia. We then compare these relationships and the observed variation in AGB and woody NPP with the predictions of four DGVM s. The observations show that stem mortality rates, rather than absolute rates of woody biomass loss, are the most important predictor of AGB , which is consistent with the importance of stand size structure for determining spatial variation in AGB . The relationship between stem mortality rates and AGB varies among different regions of Amazonia, indicating that variation in wood density and height/diameter relationships also influences AGB . In contrast to previous findings, we find that woody NPP is not correlated with stem mortality rates and is weakly positively correlated with AGB . Across the four models, basin‐wide average AGB is similar to the mean of the observations. However, the models consistently overestimate woody NPP and poorly represent the spatial patterns of both AGB and woody NPP estimated using plot data. In marked contrast to the observations, DGVM s typically show strong positive relationships between woody NPP and AGB . Resolving these differences will require incorporating forest size structure, mechanistic models of stem mortality and variation in functional composition in DGVM s.

Influence of Hydropower Development on Flow Regime in the Zambezi River Basin for Different Scenarios of Environmental Flows - T. Cohen Liechti; J. P. Matos; J.-L. Boillat; A. J. Schleiss (Water Resources Management, 2015)

Hemagglutinin variants of influenza A(H1N1)pdm09 virus with reduced affinity for sialic acid receptors - G. Ayora-Talavera; L. Cetina-Montejo; A. Matos-Patrón; L. Romero-Beltrán (Archives of Virology, 2014)

Reproducibility of Positive Results for the Detection of Serum Galactomannan by Platelia™ Aspergillus EIA - Kelly C. M. C. Pedroza; Sócrates B. de Matos; Daniel L. de Moura; Mônica B. B. Oliveira; Marco A. S. Araújo; Roberto J. M. Nascimento; Fernanda W. M. Lima (Mycopathologia, 2013)

Does the magnocellular octaval nucleus process auditory information in the toadfish, Opsanus tau? - Peggy L. Edds-Walton; Solymar Rivera Matos; Richard R. Fay (Journal of Comparative Physiology A, 2013)

Pilot monitoring study of ibuprofen in surface waters of north of Portugal - Paula Paíga; Lúcia H. M. L. M. Santos; Célia G. Amorim; Alberto N. Araújo; M. Conceição B. S. M. Montenegro; Angelina Pena; Cristina Delerue-Matos (Environmental Science and Pollution Research, 2013)

Sigma virus and male reproductive success in Drosophila melanogaster - Clare C. Rittschof; Swetapadma Pattanaik; Laura Johnson; Luis F. Matos; Jérémie Brusini; Marta L. Wayne (Behavioral Ecology and Sociobiology, 2013)

Euptychia boulleti (Le Cerf) n. comb. (Lepidoptera: Nymphalidae: Satyrinae), a Rare and Endangered Butterfly from Southeastern Brazil - A V L Freitas; N Wahlberg; P F Matos-Maravi; M A Marin; O H H Mielke (Neotropical Entomology, 2012)

Evaluation of respiratory chain activity in lymphocytes of patients with Alzheimer disease - Pollyana Feldhaus; Daiane B. Fraga; Fernando V. Ghedim; Renata D. De Luca; Thiago D. Bruna; Matheus Heluany; Maria Paula Matos; Gabriela K. Ferreira; Isabela C. Jeremias; Claudia Heluany; Emilio L. Streck; Alexandra I. Zugno (Metabolic Brain Disease, 2011)

Alcohol and tobacco, and the risk of cancers of the upper aerodigestive tract in Latin America: a case–control study - K. Szymańska; R. J. Hung; V. Wünsch-Filho; J. Eluf-Neto; M. P. Curado; S. Koifman; E. Matos; A. Menezes; L. Fernandez; A. W. Daudt; P. Boffetta; P. Brennan (Cancer Causes & Control, 2011)

Two distinct, geographically overlapping lineages of the corallimorpharian Ricordea florida (Cnidaria: Hexacorallia: Ricordeidae) - H. Torres-Pratts; T. Lado-Insua; A. L. Rhyne; L. Rodríguez-Matos; N. V. Schizas (Coral Reefs, 2011)

Behavioral changes and mitochondrial dysfunction in a rat model of schizophrenia induced by ketamine - Larissa de Oliveira; Daiane B. Fraga; Renata D. De Luca; Leila Canever; Fernando V. Ghedim; Maria Paula P. Matos; Emilio L. Streck; João Quevedo; Alexandra I. Zugno (Metabolic Brain Disease, 2011)

SacRALF1, a peptide signal from the grass sugarcane (Saccharum spp.), is potentially involved in the regulation of tissue expansion - Fabiana B. Mingossi; Juliana L. Matos; Ana Paula Rizzato; Ane H. Medeiros; Maria C. Falco; Marcio C. Silva-Filho; Daniel S. Moura (Plant Molecular Biology, 2010)

Comparative anticonvulsant activities of the essential oils (EOs) from Cymbopogon winterianus Jowitt and Cymbopogon citratus (DC) Stapf. in mice - Monalisa Ribeiro Silva; Rafael Matos Ximenes; José Galberto Martins da Costa; L. Kalyne A. M. Leal; Amanda A. de Lopes; Glauce Socorro de Barros Viana (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

An anti-inflammatory lectin from Luetzelburgia auriculata seeds inhibits adhesion and rolling of leukocytes and modulates histamine and PGE2 action in acute inflammation models - N. M. N. Alencar; R. S. B. Oliveira; J. G. Figueiredo; I. J. M. Cavalcante; M. P. V. Matos; F. Q. Cunha; J. V. S. Nunes; L. R. Bomfim; M. V. Ramos (Inflammation Research, 2010)

Scaleprinting: individual identification based on scale patterns - M. Morgado‐Santos; I. Matos; L. Vicente; M. J. Collares‐Pereira (Journal of Fish Biology, 2010)
A non‐intrusive method for individual identification of Iberian cyprinid complex Squalius alburnoides is presented, with possible application to other fish complexes and species. The proposed methodology is based on scale patterns that vary greatly between individuals.

Evaluation of metabisulfite and a commercial steel wool for removing chromium(VI) from wastewater - Caio F. Gromboni; George L. Donati; Wladiana O. Matos; Eduardo F. A. Neves; Ana Rita A. Nogueira; Joaquim A. Nóbrega (Environmental Chemistry Letters, 2010)

sTNFR-1 is an early inflammatory marker in community versus institutionalized elderly women - Fernanda Matos Coelho; F. M. S. Narciso; D. M. G. Oliveira; D. S. Pereira; A. L. Teixeira; M. M. Teixeira; D. G. Souza; L. S. M. Pereira (Inflammation Research, 2010)

Impact of Acid Mine Drainage (AMD) on Water Quality, Stream Sediments and Periphytic Diatom Communities in the Surrounding Streams of Aljustrel Mining Area (Portugal) - A. T. Luís; P. Teixeira; S. F. P. Almeida; L. Ector; J. X. Matos; E. A. Ferreira da Silva (Water, Air, & Soil Pollution, 2009)

Variable number tandem repeat loci providing discrimination within widespread genotypes of Acinetobacter baumannii - J. F. Turton; J. Matos; M. E. Kaufmann; T. L. Pitt (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Environmental assessment of water-courses of the Turvo Limpo River basin at the Minas Gerais State, Brazil - C. P. Jordão; P. R. S. Ribeiro; A. T. Matos; R. K. X. Bastos; R. B. A. Fernandes; R. L. F. Fontes (Environmental Monitoring and Assessment, 2007)

Effects of Cu, Ni and Zn on Lettuce Grown in Metal-Enriched Vermicompost Amended Soil - C. P. Jordão; L. L. Fialho; P. R. Cecon; A. T. Matos; J. C. L. Neves; E. S. Mendonça; R. L. F. Fontes (Water, Air, & Soil Pollution, 2006)

Cholesterol depletion by methyl-?-cyclodextrin enhances myoblast fusion and induces the formation of myotubes with disorganized nuclei - Cludia S. Mermelstein; Dbora M. Portilho; Rommel B. Medeiros; Aline R. Matos; Marcelo Einicker-Lamas; Giovane G. Tortelote; Adalberto Vieyra; Manoel L. Costa (Cell and Tissue Research, 2005)

Assessment of Water Systems for Contaminants from Domestic and Industrial Sewages - C. P. Jordão; M. G. Pereira; C. R. Bellato; J. L. Pereira; A. T. Matos (Environmental Monitoring and Assessment, 2002)

Effect of Oral Washes on the Diagnosis of Pneumocystis carinii Pneumonia with a Low Parasite Burden and on Detection of Organisms in Subclinical Infections - O. Matos; M. Costa; B. Lundgren; L. Caldeira; P. Aguiar; F. Antunes (European Journal of Clinical Microbiology & Infectious Diseases, 2001)

A case of multiple mating in stingless bees (Meliponinae) - V. L. Imperatriz-Fonseca; E. T. Matos; F. Ferreira; H. H. W. Velthuis (Insectes Sociaux, 1998)

Geology and geophysics as successful tools in the discovery of the Lagoa Salgada Orebody (Sado Tertiary Basin - Iberian Pyrite Belt), Grndola, Portugal - V. Oliveira; J. Matos; M. Bengala; N. Silva; P. Sousa; L. Torres (Mineralium Deposita, 1997)